LOVE OBSESSION IN GASTON LEROUX’S THE PHANTOM OF THE OPERA - Meica Angellia; Dwi Aji Prajoko (Humaniora Scientia, 2017)
This research was aimed to find out the way Erik conducts his love obsession towards Christine Daae in The Phantom of The Opera, and to find out the effects of Erik’s love obsession toward  himself  and  Christine  Daae’s  life.  This research  was  descriptive.  The  data  of  this research were words, phrases, clauses, paragraphs, or discourses containing love obsession in the  novel  The  Phantom  of  The  Opera  written  by  Gaston  Leroux.  The  source  of  data  was document, namely a novel entitled The Phantom of The Opera. The technique of collecting the data was document analysis. Moreover, sociological approach and psychological approach were applied to decide the strategy in analyzing the love obsession and the effect found in the novel. The analysis shows that: (1) the way Erik conducts his love obsession by ruling Christine Daae and trying to do anything to get Christine Daae. Furthermore, (2) the effect towards Christine’s life  is  she  is  being  oppressed  and  the  effect  toward  Erik  is  he  is  become  depressed.  The conclusion  is  people  who  suffer  from  love   obsession  can  do  negative  things  such  as, manipulating, sabotaging, threatening, setting a trap and  kidnapping. The effects can be bad such as, being oppressed for the object of love obsession and getting depressed for the person suffering from love obsession.     Keywords: Love Obsession, Obsession, Psychology